(untitled) (Proceedings of International Conference on Special Education, 2019)
Cases in the field, that involves a 5-year-old children with Down syndrome who are not able to optimize some aspects of their motor skills. The research aims to improve children’s fine motor skills in daily activities. To achieve that goal the researcher implemented a motion development training program. This study is a Single Subject Research (SSR) with A-B-A design. Data collection uses tests and observations. The data obtained was analyzed using simple descriptive statistics displayed in tables and graphs. The results showed that there was an increase in fine motor abilities of the subjects after being given a bringing up training intervention. The subject’s ability increased from 45.8% at baseline 1 (A) to 70.8% at baseline 2 (A ’). The results indicated that, motor development interventions are effective in improving motor skills.